THE EFFECT OF SCHEMA ACTIVATION STRATEGY IN COMPREHENDING NARRATIVE TEXT OF THIRD YEAR STUDENTS OF SMP DWI SEJAHTERA PEKANBARU - Nova Rina; Erni Erni; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental research was aimed at finding out whether there was a significant effect of Schema Activation Strategy in comprehending Narrative Text of third-year students’ of SMP Dwi Sejahtera Pekanbaru. The research design was one group pre-test post-test design. The population was the third-year students in academic year 2018/2019. The sample was 24 students out of the population, chosen by cluster sampling. The instrument used to collect the data was a reading test. The tests consisted of 25 items. The obtained data was analyzed by using SPSS version 20.0. The finding of the research showed that the mean score of post-test was higher than pre-test (75>60.667). The value of t-test was higher than t-table (14.922>2.07) at 5% of significance level. Therefore, alternative hypothesis (Ha) was accepted. This means that Schema Activation Strategy was effective for teaching reading comprehension concerning narrative text. There is a significant effect of Schema Activation Strategy in Comprehending Narrative Text of Third Year Students of SMP Dwi Sejahtera Pekanbaru.Keywords: Schema Activation Strategy, Reading Comprehension, Narrative Text